STRATEGI PENGELOLAAN KAWASAN EKONOMI KHUSUS (KEK) SEI MANGKEI, KLASTER INDUSTRI HILIR KELAPA SAWIT TERINTEGRASI DAN BERKELANJUTAN - Muhammad Riza Febriano; Hariyadi Hariyadi; A Roby Falatehan (JURNAL AGRICA, 2017)
Sei Mangkei Special Economic Zone (SEZ) have been designed by Government of Indonesia as industrial cluster for palm oil derivative product industries. In many cases, selected areas for industrial cluster developed into an industrial aglomeration than industrial clustering. To ensure industrial cluster accomplishment, sustainability and integration analysis should be done. The aim of paper was to conduct management strategic, sustainability and integration analysis of Sei Mangkei SEZ cluster development.  Multicriteria Decision Making (MDM) analithycal  hierarchy processs (AHP) was used to determine the value of strategic priority index. There considered for measuring the index categorized in 5 dimensions : economic, social, enviromental/ecological, laws regulations and institutional, industrial and technology. The index score of sustainability priority index of Sei Mangkei SEZ that showing that the industrial cluster development categorized as sufficient category. The lowest index was found for industrial and technology (0.195) and the highest was environment/ecological dimension and economic dimension (0.236). From the leverage analysis, some critical attributes in each dimensions were found and need improvement to increase the management strategic of Sei Mangkei SEZ into sustainability and integration. Institutional strengthening and accelerated development of infrastructure are the crucial factor should be prioritized for the development of palm oil based industrial cluster at Sei Mangkei SEZ. This could be a significant reference for the decision makers, in this case is Government (PTPN III State-Owned Enterprises and Administrator) in cooperation with private sectors (tenant) to develop Sei Mangkei SEZ